THE STORY OF ABRAHAM’S PREACHING IN ALQURAN - Faqihudin, Didin (Hunafa: Jurnal Studia Islamika, 2010)
Abraham  is a prophet whose  name is  celebrated by Jews, Christians, and Muslims, something that is not owned by the other prophets. The three religious adherents have their own story about Abraham based on their own holy scriptures. This article deals with one side of Abraham's life history, namely how  Abraham conveid God's message to his nation. This problem will be discussed in the Islamic perspective, with reference to the Koran as its main source.Key Word: Abraham, Alquran, preaching